Fluoropolymer and Liquid Crystal Polymer Blends

The LCP/FP blends, enhanced by a reactive polymer compatibility agent, address mechanical weaknesses and thermal expansion issues of fluoropolymers, offering enhanced mechanical and thermal properties for high-performance PCBs.

JP7623474B2Active Publication Date: 2025-01-28DAIKIN AMERICA INC +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023514755
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-04
Filing Date
2021-09-03
Publication Date
2025-01-28
Estimated Expiration
2041-09-03

AI Technical Summary

Technical Problem

Fluoropolymers exhibit excellent chemical resistance and heat resistance but have weak mechanical properties, making them unsuitable for high-performance PCB applications, and blending with LCD polymers results in poor mechanical properties and thermal expansion issues.

Method used

A blend of LCD polymer (LCP) and fluoropolymers (FP) is developed, enhanced by a reactive polymer compatibility agent (RPC) containing fluorine-containing and non-fluorine-containing monomers, which improves mechanical properties and reduces thermal expansion.

Benefits of technology

The LCP/FP blends demonstrate improved mechanical properties, reduced thermal expansion, and maintained thermal properties, suitable for high-speed, high-frequency PCB applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623474000033
    Figure 0007623474000033
  • Figure 0007623474000034
    Figure 0007623474000034
  • Figure 0007623474000035
    Figure 0007623474000035
Patent Text Reader

Abstract

A polymer blend of a fluoropolymer and a liquid crystal polymer is provided. The blend is obtained using a compatibilizer composition comprising a copolymer containing a fluorine-containing monomer and a liquid crystal monomer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims the benefit of U.S. Provisional Application No. 63 / 074,631, filed September 4, 2020, which is incorporated herein by reference in its entirety.

[0002] The present disclosure relates generally to polymer blends, methods of making polymer blends, methods of using polymer blends, compatibilizer compositions for use with polymer blends, and articles made from polymer blends. [Background technology]

[0003] A printed circuit board (PCB) is an integrated assembly of many electronic components. PCBs physically support and connect electrical components with conductive paths etched from copper sheet layers and laminated onto and / or between non-conductive substrate sheet layers. PCBs can be rigid, flexible, or rigid-flexible, each with multiple laminates made from thermoplastic or thermoset polymeric materials. Materials used in PCB laminates are often classified by their dielectric constant (Dk) and dissipation factor (Df) values. The highest performance materials have the lowest Dk and Df.

[0004] Low Dk and Df values ​​are useful properties for high-speed digital and high-frequency PCBs used in various emerging markets such as autonomous driving and fifth generation wireless communication (5G) devices (e.g., radio frequency components, power amplifiers, and antennas). Thermoplastic laminates with low dielectric loss tangent (Df) can be used in high-frequency PCBs to meet high-power applications and reduce heat-generating energy losses that degrade signal quality. Laminates with low dielectric constant (Dk) are also important for achieving high-speed signal propagation in high-speed digital PCBs.

[0005] In general, fluoropolymers (FPs) have excellent heat resistance, chemical resistance, and non-stick properties. Although fluoropolymers exhibit excellent chemical properties, they have relatively weak mechanical properties compared to specialty materials such as liquid crystal polymers (LCPs) and polyimides (PIs) used in high-performance PCB applications. In addition, fluoropolymers have low surface energy and high coefficient of thermal expansion (CTE), making it difficult to incorporate these materials into PCB laminates.

[0006] Due to the poor compatibility of FP with other polymers, attempts to blend them have resulted in mixtures with poor structural integrity. Thus, there remains a need in the art for fluorine-containing polymer compositions with improved mechanical properties for use in high speed and high frequency PCB laminates, etc. Summary of the Invention

[0007] This disclosure describes blends of LCPs and FPs that address the above challenges with superior properties over either LCPs or FPs. Also described are compatibilizer compositions for use in such blends. Some embodiments of LCP / FP blends form thermoplastic alloys with significantly improved mechanical properties and significantly reduced coefficient of thermal expansion relative to liquid crystal polymers while retaining thermal properties and improved electrical properties (particularly dielectric constant and dissipation factor).

[0008] In a first aspect, a copolymer is provided that includes a fluorine-containing monomer and a liquid crystal monomer.

[0009] In a second aspect, a compatibilizer composition is provided that includes a copolymer of a fluorine-containing monomer and a liquid crystal monomer.

[0010] In a third aspect, there is provided a polymer blend comprising a fluoropolymer, a liquid crystalline polymer, and a compatibilizer composition, wherein the compatibilizer composition comprises a copolymer comprising a fluorinated or non-fluorinated monomer and a liquid crystalline monomer.

[0011] In a fourth aspect, there is provided a process for making a compatibilizer composition comprising mixing a fluoropolymer with a functionalized fluorinated molecule and a liquid crystal monomer to form a copolymer, and mixing a fully fluorinated fluoropolymer, a fluorinated molecule, and a liquid crystal monomer in an extruder to form the compatibilizer composition.

[0012] In a fifth aspect, there is provided a process for producing a compatibilizer composition comprising mixing a non-fluorinated polymer with a liquid crystalline monomer to produce a copolymer, and mixing the components of the copolymer in an extruder to produce the compatibilizer composition.

[0013] In a sixth aspect, a process for producing a compatibilized blend of a liquid crystal polymer (LCP) and a fluoropolymer (FP) is provided, the process comprising combining the LCP and the FP with a compatibilizer composition comprising a copolymer of a fluorine-containing molecule and a liquid crystal monomer.

[0014] In a seventh aspect, there is provided a compatibilizer composition that is the product of a process having the steps of mixing a fully fluorinated fluoropolymer with a fluorinated molecule, and a liquid crystal monomer to form a copolymer, and mixing the copolymer blend in an extruder to form the compatibilizer composition.

[0015] In an eighth aspect, there is provided a compatibilizer composition that is the product of a process having the steps of mixing a non-fluorinated fluoropolymer with a liquid crystalline monomer to form a copolymer, and mixing the components of said copolymer in an extruder to form a compatibilizer composition.

[0016] In a ninth aspect, there is provided a compatibilized blend of a liquid crystal polymer (LCP) and a fluoropolymer (FP), the compatibilized blend being the product of a process comprising combining the LCP and the FP with a compatibilizer composition comprising a copolymer of a fluorine-containing molecule and a liquid crystal monomer.

[0017] In a tenth aspect, an article of manufacture is provided comprising any of the above compositions.

[0018] The foregoing is a simplified summary presented to provide a basic understanding of some aspects of the claimed subject matter. This summary is not an exhaustive overview. It is not intended to identify key or critical elements or to delineate the scope of the claimed subject matter. Its sole purpose is to present some concepts in a simplified form as a prelude to the more detailed description that is presented later. [Brief description of the drawings]

[0019] [Figure 1] 1 illustrates an example of a scheme for making a compatibilizer composition or reactive polymer compatibilizer containing FEP. [Diagram 2] 1 depicts a scanning electron micrograph taken at 1500x of one embodiment of a reactive polymer compatibilizer. [Diagram 3] 1 depicts a scanning electron micrograph taken at 2000x of one embodiment of a reactive polymer compatibilizer. [Figure 4] 1 shows the tensile modulus of one embodiment of FEP, LCP, and a blend of FEP and LCP. [Diagram 5] 1 shows the coefficient of thermal expansion (CTE) at 100° C. of one embodiment of FEP, LCP, and a blend of FEP and LCP. [Figure 6] 1 shows the thermal stability as measured by loss in nitrogen for one embodiment of FEP, LCP, and a blend of FEP and LCP. The Y-axis is the temperature at which a 5% weight loss is observed. [Figure 7] 1 shows the glass transition temperatures of one embodiment of FEP, LCP, and a blend of FEP and LCP. [Figure 8] 1 shows the flexural stress at maximum flexural load for one embodiment of FEP, LCP, and a blend of FEP and LCP, where the maximum flexural load for the blend is lower than the unblended LCP. [Figure 9] 1 shows the flexural modulus of one embodiment of FEP, LCP, and a blend of FEP and LCP, where the flexural modulus of the blend is lower than that of the unblended LCP. [Figure 10] 1 shows the ultimate tensile strength of films made from embodiments blending FEP and LCP compared to FEP alone. [Figure 11] The Young's modulus of films made from an embodiment blending FEP and LCP is compared to FEP alone. [Figure 12] The maximum bending load of films made from an embodiment of a blend of FEP and LCP is compared to FEP alone. [Figure 13] The flexural modulus of a thin film made from an embodiment in which FEP and LCP are blended is compared to that of FEP alone. [Figure 14] The thermal expansion coefficients at five temperatures of films made from an embodiment of a blend of FEP and LCP are compared to FEP alone. [Figure 15] 1 illustrates an example of a scheme for producing a reactive polymeric compatibilizer containing PFA. [Figure 16] 1 shows an example of the structure of a cyclic olefin copolymer. [Figure 17] 1 illustrates the tensile strength of LCP and FP blends according to one embodiment. [Figure 18] 1 shows the tensile modulus of LCP and FP blends according to one embodiment. [Figure 19] 1 shows the elongation at break of LCP and FP blends according to one embodiment. [Figure 20] 1 shows the CTE of LCP and FP blends according to one embodiment. [Figure 21] 1 illustrates the dielectric constant of LCP and FP blends according to one embodiment. [Figure 22] 1 illustrates the dielectric loss of LCP and FP blends according to one embodiment. [Figure 23] 1 shows an SEM photograph of the pellet of sample 90A taken at 1300x magnification in the flow direction. [Figure 24] 1 shows an SEM photograph of the pellet of sample 92C taken at 1300x magnification in the flow direction. [Diagram 25]1 shows an SEM photograph of the pellet of sample 92D taken at 1300x magnification in the flow direction. [Figure 26] 1 illustrates the tensile strength of LCP and FP blends according to one embodiment. [Figure 27] 1 shows the tensile modulus of LCP and FP blends according to one embodiment. [Figure 28] 1 shows the elongation at break of LCP and FP blends according to one embodiment. [Figure 29] 1 depicts the dimensional change in the Z direction of an LCP and FP blend according to one embodiment. [Diagram 30] 14 depicts the CTE in the Z-direction of injection molded parts, measured as the slope of the line of best fit to the data over the temperature ranges 10-100° C. and 100-200° C., for LCP and FP blends according to one embodiment. [Diagram 31] 1 shows the dielectric constant of an embodiment of an LCP and FP blend measured at 16 GHz using a split cavity method. [Diagram 32] 1 shows the dielectric loss of an embodiment of an LCP and FP blend measured at 16 GHz using the split cavity technique. [Diagram 33] 1 represents the tensile strength according to an embodiment. [Diagram 34] 4 illustrates the tensile modulus according to an embodiment. [Diagram 35] 4 illustrates the elongation at break according to an embodiment. [Diagram 36] 4 illustrates the flexural modulus according to an embodiment. [Figure 37] 1 shows the dielectric constant of an embodiment measured at 16 GHz using a split cavity technique. [Figure 38] 1 shows the dielectric loss of an embodiment measured at 16 GHz using a split cavity technique. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] A. definition

[0021] Unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by those skilled in the art in the field of this disclosure. Furthermore, it should be understood that terms defined in commonly used dictionaries should be interpreted as having a meaning consistent with the meaning in the context of the specification, and should not be interpreted in an idealized or overly formal sense unless explicitly defined in the specification. For the sake of brevity and clarity, well-known functions and configurations are not described in detail.

[0022] The terms "about" and "approximately" generally refer to an acceptable degree of error or variation in a measured quantity, given the nature or precision of the measurement. Typical degrees of error or variation include, for example, within 20 percent (%), preferably within 10%, more preferably within 5%, and even more preferably within 1% of a given numerical value or range of values. Unless otherwise stated, numerical values ​​given herein are approximate. That is, the term "about" or "approximately" is presumed when not expressly stated.

[0023] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting. As used herein, the singular forms "a," "an," and "the" are intended to include the plural forms (i.e., "at least one") unless the context clearly indicates otherwise.

[0024] In this specification, terms such as "first" and "second" are used to describe various features or elements, but these features or elements should not be limited by these terms. These terms are used only to distinguish one feature or element from another. Thus, a first feature or element described below can be referred to as a second feature or element, and similarly, a second feature or element described below can be referred to as a first feature or element, without departing from the teachings of the present disclosure.

[0025] A phrase such as "at least one of A and B" should be understood to mean "A only, B only, or both A and B." The same interpretation applies to longer lists (e.g., "at least one of A, B, and C").

[0026] The term "consisting essentially of" means that the claimed subject matter may include, in addition to the recited elements, other elements (steps, structures, components, members, etc.) that do not adversely affect the operability of the claimed subject matter for its intended purposes as recited in this disclosure. The term excludes other elements that adversely affect the operability of the claimed subject matter for its intended purposes as recited in this disclosure, even if such other elements may enhance the operability of the claimed subject matter for some other purpose.

[0027] In some places, reference is made to standard methodologies, including but not limited to measurement methods. It is understood that such standards are revised from time to time and, unless expressly stated otherwise, references in this disclosure to such standards shall be construed as referring to the most recently published standard at the time of filing.

[0028] It will be understood that certain elements in the disclosed embodiments of the present invention may be embodied in a single structure, a single step, or a single material, etc. Likewise, certain elements in the disclosed embodiments may be embodied in multiple structures, steps, or materials, etc.

[0029] B. Reactive Polymer Compatibilizer Copolymer

[0030] Copolymers are described that facilitate the formation of blends of FPs and LCPs. Such copolymers are also referred to as reactive polymeric compatibilizers (RPCs). RPCs contain at least two monomers. In some embodiments, these monomers are composed of different types of monomers: fluorinated molecules and non-fluorinated monomers.

[0031] In some embodiments, RPCs can be produced by mixing functionalized fluoropolymers with non-fluorinated monomers in an extruder. The functional groups make the RPC copolymers more amenable to polymerization. Typically, functional groups are moieties that contain oxygen and / or nitrogen. Functional groups useful for facilitating polymerization include carboxyl, hydroxy, epoxy, amine, carboxyl ester, ester, and COF.

[0032] A functionalized fluoropolymer includes multiple functionalized monomers. A given functionalized monomer may have two or more functional groups, which may be the same or different. For example, a monomer may include two carboxyl moieties. In yet another embodiment of the RPC copolymer, the fluorine-containing monomer may include carboxyl and hydroxyl, carboxyl and epoxy, carboxyl and amine, carboxyl and carboxyl ester, carboxyl and ester, and carboxyl and COF. In yet another embodiment of the RPC copolymer, the fluorine-containing monomer may include hydroxyl and epoxy, hydroxyl and amine, hydroxyl and carboxyl ester, hydroxyl and ester, and hydroxyl and COF. In yet another embodiment of the RPC copolymer, the fluorine-containing monomer may include epoxy and amine, epoxy and carboxyl ester, epoxy and ester, and epoxy and COF. In yet another embodiment of the RPC copolymer, the fluorine-containing monomer may include amine and carboxyl ester, amine and ester, and amine and COF. In yet another embodiment of the RPC copolymer, the fluorine-containing monomer may include carboxyl ester and ester, and carboxyl ester and COF. In yet another embodiment of the RPC copolymer, the fluorine-containing monomer may include esters and COFs. In a preferred embodiment, the fluorine-containing monomer has two functional groups. Yet another embodiment of the fluorine-containing monomer may have one to six functional groups. Specific embodiments of the fluorine-containing monomer have one, two, three, four, five, or six functional groups.

[0033] In some embodiments, the fluorine-containing molecule is fully fluorinated (i.e., composed of fluorine and carbon) except for one or more functional groups. Some embodiments of the fluorine-containing monomer are composed of carbon saturated with fluorine except for the functional groups. In other embodiments, one or more double or triple bonds may be present. Specific examples of suitable fluoropolymer molecules include fluorinated ethylene propylene (FEP), functionalized FEP, perfluoroalkoxyalkane (PFA), functionalized PFA, tetrafluoroethylene-perfluoroalkylvinylether copolymer, functionalized tetrafluoroethylene-perfluoroalkylvinylether copolymer, ethylene-tetrafluoroethylene (ETFE), functionalized ETFE, polychlorotrifluoroethylene (PCTFE), and functionalized PCTFE. In one embodiment, the fluorinated molecule is a dicarboxy FEP, such as the structure shown below: [ka] where m and n are at least 1. In another embodiment, the fluorinated molecule is a dicarboxytetraethylene-perfluoro(alkyl vinyl ether) copolymer, such as the structure shown below. [ka] wherein m and n are at least 1.

[0034] In some embodiments, the non-fluorinated monomer is a monomer of a liquid crystal polymer. In this case, the monomer of the liquid crystal polymer may be any monomer of any liquid crystal polymer known in the art, or may be an aromatic compound having at least two functional groups. The aromatic compound may be a single-ring aromatic compound or a multi-ring aromatic compound. A specific embodiment of the non-fluorinated monomer is a single-ring aromatic compound or a two-ring aromatic compound. Examples of suitable liquid crystal monomers are shown below, but are not limited thereto. [ka]

[0035] In yet another embodiment of the liquid crystal monomer, the monomer is a specific LCP monomer such as polyparaphenylene terephthalamide (KEVLAR®). In an embodiment where the liquid crystal monomer is a KEVLAR® monomer, the RPC copolymer may include one or both of the monomers 1,4-phenylene-diamine (para-phenylenediamine) and terephthaloyl chloride. Another embodiment of the copolymer may include a monomer of VECTRAN, an aromatic polyester LCP having the following structure: [ka] where x and y are at least 1. In such embodiments, the RPC copolymer may include one or both of the monomers 4-hydroxybenzoic acid and 6-hydroxynaphthalene-2-carboxylic acid. The non-fluorinated monomers listed above can be present in any combination. The RPC copolymer may include multiple non-fluorinated or LCP monomers. Various embodiments of the copolymer may include 1 to 12 non-fluorinated or LCP monomers. Particular embodiments of the RPC copolymer include one non-fluorinated monomer or two fluorinated monomers. In some embodiments, the RPC copolymer includes the same type of liquid crystal monomer as the LCP in the LCP / FP blend.

[0036] In yet another embodiment, the RPC copolymer comprises three types of molecules: a fluorinated molecule, a non-fluorinated monomer, and a linking molecule. The linking molecule is selected for its molecular flexibility. The linking molecule may have molecular flexibility by including an aliphatic chain or an ether functionality. In some embodiments, the linking molecule is derived from a polymeric rubber. In some embodiments, the linking molecule includes a reactive functional group such as an amine, a carboxylic acid, an ester, or anhydride. In some embodiments, the linking molecule includes at least two reactive functional groups. In some embodiments of the RPC copolymer, the non-fluorinated monomer may be selected from the LCP monomer species described herein.

[0037] In some embodiments, the RPC copolymer contains only non-fluorinated moieties. In these embodiments, there are two, three, or more types of non-fluorinated molecules in the copolymer. In disclosed embodiments, one of these types of monomers is the LCP monomer described above. In some embodiments, molecules containing linking moieties with molecular flexibility may be used. In some embodiments, the non-fluorinated monomers are functionalized to add reactive functional groups to the polymer, such as amines, anhydrides, carboxylic acids, or hydroxys. In some embodiments, the functional groups on the non-fluorinated polymer are selected to react easily with the functional groups on the flexible linking molecule.

[0038] In some embodiments of the RPC copolymer, the fluorine-containing molecules will be present in a weight ratio relative to the non-fluorinated molecules. For example, when the fluorine-containing molecules are present in the same weight concentration as the non-fluorinated molecules, the ratio of fluorine-containing molecules to non-fluorinated molecules is 1:1. In some embodiments of the copolymer, the ratio of fluorine-containing molecules to non-fluorinated molecules is 1:10 to 10:1. In yet other embodiments of the RPC copolymer, the ratio is 1:10 to 3:1, 1:10 to 1:1, 1:10 to 1:3, 1:3 to 1:1, 1:3 to 3:1, 1:3 to 10:1, 1:1 to 3:1, 1:1 to 10:1, or 3:1 to 10:1. In specific embodiments of the RPC copolymer, the ratio of fluorine-containing molecules to non-fluorinated molecules is 1:10, 1:3, 1:1, 3:1, and 10:1. Here, the term "fluorine-containing molecule" can refer to a plurality of fluorine-containing molecules that together constitute the fluorine-containing molecular portion of the copolymer. Similarly, the term "non-fluorinated molecule" can refer to a plurality of non-fluorinated molecules that together constitute the non-fluorinated molecular portion of the copolymer.

[0039] C. Compatibilizer composition

[0040] A compatibilizer composition useful for compatibilizing LCPs and FPs is described, which comprises the RPC copolymer described above.

[0041] In a preferred embodiment, the compatibilizer composition is a compatibilizer blend that includes a predetermined amount of fluoropolymer. The fluoropolymer can be selected based on the properties of the fluoropolymer in the final FP / LCP blend (described in more detail below). In some embodiments of the compatibilizer blend, the fluoropolymer is the same compound as the fluoropolymer in the final FP / LCP blend. The fluoropolymer in the compatibilizer blend can be partially fluorinated or fully fluorinated. In one preferred embodiment, it is fully fluorinated. In some such embodiments, the fluoropolymer in the compatibilizer blend does not have functional groups, thereby preventing it from participating in the polymerization reaction during the formation of the RPC copolymer. Here, "functional groups" refers to the same moieties as described above with respect to the fluorinated molecules of the RPC copolymer. Specific examples of suitable non-functionalized fluoropolymers in the compatibilizer blend include FEP, PFA, ETFE, PTFE, PVF, PVDF, PCTFE, ECTFE, FFPM / FFKM, FPM / FKM, FEPM, PFPE, PFSA, and combinations of two or more thereof. In one specific embodiment, the non-functionalized fluoropolymer is FEP. In a more specific embodiment, the non-functionalized fluoropolymer is PFA.

[0042] The small molecule compatibilizer may be added to the compatibilizer composition, but in some embodiments of the LCP / FP blend, the compatibilizer composition is prepared before the small molecule compatibilizer is added to the blend. A variety of small molecule compatibilizers can be used, including, but not limited to, bis(oxazoline) compounds, carbonyldiimidazole compounds, and epoxy compounds. In a preferred embodiment, the small molecule compatibilizer is 1,1'-carbonyldiimidazole. In another preferred embodiment, the small molecule compatibilizer is 1,3-phenylene-bis-oxazoline. Other suitable small molecule compatibilizers are listed below. [ka] [ka]

[0043] The small molecule compatibilizer can be present in a variety of concentrations: 0.01-5.0%, 0.02-4.5%, 0.03-4.0%, 0.05-3.5%, 0.07-3.0%, 0.1-2.5%, 0.3-2.0%, 0.5-1.5%, 0.8-1.2%, and 1% when measured as weight percent of monomer, fluoropolymer, RPC compatibilizer, and small molecule compatibilizer.

[0044] The compatibilizer composition can be prepared in a variety of ways. A method for producing the compatibilizer composition is described, which includes mixing a fully fluorinated fluoropolymer with a fluorinated molecule having reactive groups and a liquid crystal monomer to produce an RPC copolymer, and mixing the copolymer in an extruder to produce the compatibilizer composition. Polymerization of the fluorinated monomer and the liquid crystal monomer occurs during the extrusion of such a process. Some embodiments of the RPC copolymer are suitable for storage for later use, but in some embodiments of the above process, the RPC copolymer blend is added to the mixture of LCP and FP immediately after production.

[0045] The RPC copolymer may include one or more functionalized fluorinated monomers and one or more LCP monomers. These may be the monomers or molecules described above as suitable for incorporation into an LCP / FP RPC. In some embodiments, these monomers or molecules may be present in the RPC copolymer in the relative amounts described above.

[0046] D. Polymer Blends

[0047] Some embodiments of the RPC copolymers and compatibilizers described above are useful in compatibilized blends of LCPs and FPs. Many of the resulting polymer blends have good mechanical properties (similar to pure LCPs) along with good chemical resistance (similar to pure FPs). Various FPs that can be used in the blends include, but are not limited to, FEP, PFA, ETFE, PTFE, PVF, PVDF, PCTFE, ECTFE, FFPM / FFKM, FPM / FKM, FEPM, PFPE, PFSA, and combinations of two or more thereof. In a specific embodiment, the FP is FEP. In a more specific embodiment, the FP is PFA. Various LCPs that can be used in the blends include polyparaphenylene terephthalamide (KEVLAR®) and LCP VECTRAN. Further suitable LCPs may be polymers of 6-hydroxy-2-naphthoic acid, 4-hydroxybenzoic acid, aminobenzoic acid, aminophenol, terephthalic acid, and isoterephthalic acid. Further suitable LCPs may be copolymers of one or more of 6-hydroxy-2-naphthoic acid, 4-hydroxybenzoic acid, aminobenzoic acid, aminophenol, terephthalic acid, and isoterephthalic acid. The LCP or FP may be independently selected from random copolymers, homopolymers, block copolymers, alternating copolymers, and graft copolymers. In one specific embodiment, the LCP is a copolymer of 6-hydroxy-2-naphthoic acid and 4-hydroxybenzoic acid.

[0048] As illustrated in the examples below, suitable properties can be obtained by using various relative proportions of FP to LCP. In some embodiments of the polymer blends, the ratio of FP to LCP is 25:75 or less by weight. In other embodiments of the polymer blends, the ratio of FP:LCP is 20:80 or less by weight. In other embodiments of the polymer blends, the ratio of FP:LCP is 15:85 or less by weight. In other embodiments of the polymer blends, the ratio of FP:LCP is 10:90 or less by weight. In yet other embodiments of the polymer blends, the ratio of FP:LCP is 5:95 or less by weight. In yet other embodiments of the polymer blends, the ratio of FP:LCP is 1:20 to 1:4. In yet other embodiments of the polymer blends, the ratio of FP:LCP is 1:10 to 1:5. In yet other embodiments of the polymer blends, the ratio of FP:LCP is 1:10 to 1:5. In some embodiments of the polymer blends, the ratio of FP to LCP is 75:25 or less by weight. In another embodiment of the polymer blend, the FP:LCP ratio is 80:20 or less by weight. In another embodiment of the polymer blend, the FP:LCP ratio is 85:15 or less by weight. In another embodiment of the polymer blend, the FP:LCP ratio is 90:10 or less by weight. In yet another embodiment of the polymer blend, the FP:LCP ratio is 5:95 or less by weight. In yet another embodiment of the polymer blend, the FP:LCP ratio is 20:1 to 4:1. In yet another embodiment of the polymer blend, the FP:LCP ratio is 10:1 to 5:1.

[0049] The polymer blend may include any of the RPC copolymers described above. In some embodiments of the polymer blend, the RPC copolymer is part of a compatibilizer composition. The compatibilizer composition may be any of those described above. The compatibilizer may be present in an amount effective to compatibilize the LCP with the FP in the polymer blend. For example, the compatibilizer may be present at 30% or less by weight of the polymer blend. In another example, the compatibilizer may be present at 20% or less by weight of the polymer blend. In another example, the compatibilizer may be present at 15% or less by weight of the polymer blend. In some embodiments, the compatibilizer may be present at 1-30% by weight of the polymer blend. In some embodiments, the compatibilizer may be present at 2.5-25% by weight of the polymer blend. In some embodiments, the compatibilizer may be present at 5-15% by weight of the polymer blend.

[0050] As partially described in the examples below, the polymer blends exhibit various physical properties. Some embodiments of the polymer blends exhibit a continuous phase and do not exhibit fibrillated morphology. Some preferred embodiments of the polymer blends have a high Young's modulus. Some embodiments of the polymer blends may have a Young's modulus of at least 220, 400, 500, 600, 700, or 900 MPa. The Young's modulus of the preferred embodiments of the polymer blends is higher than the pure composition of one or more fluoropolymers in the polymer blend. The Young's modulus of the specific preferred embodiments of the polymer blends is at least 200% of the pure composition of one or more fluoropolymers in the polymer blend.

[0051] As described in part in the examples below, some embodiments of the polymer blends exhibit good ultimate tensile strength. Polymer blend embodiments may have a tensile strength of at least 20, 30, 35, 38, or 40 MPa. In a preferred embodiment, the ultimate tensile strength of the polymer blend is greater than the pure composition of the fluoropolymer.

[0052] Some embodiments of the polymer blends exhibit high elongation (% elongation at break). Some embodiments of the polymer blends have an elongation of at least 3%. Other embodiments of the polymer blends have an elongation of at least 5%. Other embodiments of the polymer blends have an elongation of at least 8%. Other embodiments of the polymer blends have an elongation of at least 70%. Other embodiments of the polymer blends have an elongation of at least 74%. In a preferred embodiment, the elongation of the polymer blend is at least the same as the pure composition of the fluoropolymer.

[0053] Some embodiments of the polymer blends exhibit a low coefficient of thermal expansion (CTE). Some embodiments of the polymer blends have a CTE at about 80°C of 180, 100, 97, or 95 ppm / °C or less. In a preferred embodiment, the CTE of the polymer blend at 80°C is lower than the pure composition of at least one fluoropolymer in the polymer blend. Some embodiments of the polymer blends have a CTE at about 100°C of 200, 195, or 95 ppm / °C or less. In a preferred embodiment, the CTE of the polymer blend at about 100°C is lower than the pure composition of at least one fluoropolymer in the polymer blend. Some embodiments of the polymer blends have a CTE at 120°C of about 200 or 150 ppm / °C or less. In a preferred embodiment, the CTE of the polymer blend at about 120°C is lower than the pure composition of at least one fluoropolymer in the polymer blend. Some embodiments of the polymer blends have a CTE at 180°C of 200 ppm / °C or less. In a preferred embodiment, the polymer blend has a lower CTE at about 180° C. than the pure composition of at least one fluoropolymer in the polymer blend. In a specific preferred embodiment, the polymer blend has a lower coefficient of thermal expansion at 80, 100, 120, 150, and 180° C. than the pure composition of at least one fluoropolymer in the polymer blend. In another specific embodiment, the polymer blend has a Young's modulus of at least 500 MPa, an elongation at break of at least 70%, and a coefficient of thermal expansion at about 100° C. of 100 ppm / ° C.

[0054] Some embodiments of the polymer blends exhibit high 5% weight loss temperatures. Some embodiments of the polymer blends have a 5% weight loss temperature in N2 of greater than 480° C. A preferred embodiment of the polymer blend has a 5% weight loss temperature in N2 that is equal to or lower than the pure composition of at least one fluoropolymer in the blend.

[0055] The polymer blend embodiments exhibit low glass transition temperatures. Some polymer blend embodiments have glass transition temperatures below 100° C. A preferred embodiment of the polymer blend has a glass transition temperature that is the same as the pure composition of at least one fluoropolymer in the polymer blend.

[0056] The polymer blend embodiments exhibit good flexural load characteristics. The flexural stress at maximum flexural load of some polymer blend embodiments is approximately the same as the pure composition of at least one fluoropolymer in the blend. Another polymer blend embodiment has a flexural modulus of greater than 600 MPa. Another polymer blend embodiment has a flexural modulus of greater than 1000 MPa. Another polymer blend embodiment has a flexural modulus of at least 120% relative to at least one pure fluoropolymer in the blend. Yet another polymer blend embodiment has a flexural modulus of at least 200% relative to at least one pure fluoropolymer in the blend. Some polymer blend embodiments have a flexural modulus of at least 800%, at least 1000%, at least 1200%, or at least 1400% relative to at least one pure fluoropolymer in the blend.

[0057] Embodiments of the polymer blends have been observed to have dielectric properties that are particularly suitable for use in electronic component applications. Some embodiments of the polymer blends have a dielectric constant of 2-3 at 10 GHz. Another embodiment of the polymer blend has a dielectric constant of about 2.1 at 10 GHz. Some embodiments of the polymer blends have a dielectric loss of less than 0.0050 at 10 GHz. Another embodiment of the polymer blend may have a dielectric loss of 0.0003-0.0050 at 10 GHz. Yet another embodiment of the polymer blend may have a dielectric loss of 0.0010 at 10 GHz. A preferred embodiment of the polymer blend has a dielectric loss at 10 GHz that is lower than the pure composition of at least one LCP in the blend. Another preferred embodiment of the polymer blend has a dielectric loss at 10 GHz that is 20% of the pure composition of at least one LCP in the blend.

[0058] Various embodiments of the polymer blends can be used to produce many types of manufactured articles. Such articles include extruded fibers that include the polymer blends. Such extruded fiber embodiments may include more than 50% by weight, at least 75% by weight, at least 80% by weight, at least 85% by weight, at least 90% by weight, at least 95% by weight, at least 96% by weight, at least 97% by weight, at least 98% by weight, at least 99% by weight, or 100% by weight of the polymer blend. Thin films have also found applications for the polymers. Such thin film embodiments may include more than 50% by weight, at least 75% by weight, at least 80% by weight, at least 85% by weight, at least 90% by weight, at least 95% by weight, at least 96% by weight, at least 97% by weight, at least 98% by weight, at least 99% by weight, or 100% by weight of the polymer blend. Other manufactured articles include insulation for communication cables, printed circuit boards, tapes, twisted pair high speed cables for automobiles, thin films for high temperature capacitors, coatings for downhole oil and gas drilling, fibers for 3D printed products, monofilaments or multifilaments for woven or nonwoven filtration substrates, proton exchange membranes and printed circuit boards, 1-1000 micron thin film substrates for printed circuit boards, wire and cable for downhole cables, tape coatings for electrical insulation, inorganic fillers for tapes (aluminum hydroxide, ceramic glass, SiO2, fluorosilicate glass), thermally conductive additives, foams for wire and cable, automobiles having any of these, electric vehicles having any of these, and airplanes having any of these. EXAMPLES

[0059] 1. Example 1: Preparation of FEP / LCP Reactive Polymer Compatibilizer To make the FEP / LCP RPC described in this Example 1, fully fluorinated FEP, carboxylated FEP, 6-hydroxy-2-naphthoic acid, and 4-hydroxybenzoic acid were all added to one bag and mixed uniformly. The amounts of each material used in the RPC are shown in Table 1. Both LCP monomers, 6-hydroxy-2-naphthoic acid and 4-hydroxybenzoic acid, were added at 1:1 molar equivalents, with a total of 5 wt% in all formulations. In Samples 2-5, the carboxylated FEP was varied from 10-75 wt% for each sample. [Table 1]

[0060] Once the samples were thoroughly mixed, the mixture was fed into a twin screw extruder (Leistritz ZSE 18 HP) at 4.0-6.0 kg / hr. For sample 1, zones 1-8 were heated to 310-340°C. For samples 2-5, zones 1-8 were heated to 300-310°C to inhibit thermal degradation. The screw speed was held constant at 250 rpm. All RPC samples were obtained as brown pellets.

[0061] FIG. 1 shows an example of a scheme for producing FEP / LCP RPC. As shown in FIG. 1, FEP / LCP RPC is prepared by polycondensation in a twin screw extruder. Step-growth polycondensation proceeds with the heat of the extruder, and HF generated from fully fluorinated FEP and / or carboxylated FEP acts as a Lewis acid to drive the reaction. The aromatic monomers 6-hydroxy-2-naphthoic acid and 4-hydroxybenzoic acid are effective in reducing the interfacial tension between fully fluorinated FEP and LCP. Since 6-hydroxy-2-naphthoic acid and 4-hydroxybenzoic acid are AB-type functional monomers, any of the monomers can be polymerized with other molecules or other monomers in the sample molecular structure. The corresponding random copolymers, monomers, and oligomers can react only with the end groups of carboxylated FEP to produce AB or ABA-type random block copolymers.

[0062] Once all samples of FEP / LCP RPC were extruded, the morphology of sample 1 (Oligo-LCP1) and sample 5 (75% EG-Oligo-LCP5) were compared under a scanning electron microscope (SEM). These two samples were chosen for comparison due to their different content of carboxylated FEP. SEM images were obtained on a Joel JSM-6010Plus SEM. Cross sections of the samples were prepared and imaged at a working distance of 10 mm and 5 kV. All images were taken at 1.0k-2.0k.

[0063] Figure 2 shows an SEM image of Sample 1 (Oligo-LCP1) taken at 1500x. The image in Figure 2 shows the presence of fibrillary morphology. Figure 3 shows an SEM image of Sample 5 (75% EG-Oligo-LCP5) taken at 2000x. The image in Figure 3 shows that there is a continuous layer throughout the sample and no fibrillated morphology is present. This indicates that Sample 5 (75% EG-Oligo-LCP5) is an AB and ABA sequential block copolymer.

[0064] 2. Example 2: Preparation of FEP / LCP Compatibilized Blends After preparing the FEP / LCP RPC samples, the block copolymer was blended with Vectra LCP A950, 75% EG-Oligo-LCP5, fully fluorinated FEP, and 1,1'-carbonyldiimidazole (CDI) in a twin screw extruder. The amounts of each component used in the various samples are shown in Table 2 below. [Table 2]

[0065] In both samples, the 75%EG-Oligo-LCP4 component acted as a compatibilizer by reducing the interfacial tension between Vectra LCP A950 and fully-fluorinated FEP and increasing the molecular adhesion between Vectra LCP A950 and fully-fluorinated FEP to produce homogeneous blends. In addition to increasing the compatibility between Vectra LCP A950 and fully-fluorinated FEP using block copolymers, CDI was employed as a reactive compatibilizer in these formulations because it can react with alcohol end groups to form new ester bonds and carboxylic acid end groups to form new anhydride bonds.

[0066] 3. Example 3: Mechanical and Thermal Properties of FEP / LCP Compatibilized Blends The mechanical and thermal properties of Samples 6-9 and TPL4000 (Table 2 above) were tested and compared to fully fluorinated FEP and Vectra LCP A950. Samples were gravity fed into a Sumitomo SE75DU injection molding machine. The feed zone was held at 49°C. Zones 1-5 were heated to 304°C-327°C. The pack time was 5.00 seconds and the pack pressure was 10.00 kpsi. The screw was retracted 0.3 inches at a rate of 0.2 inches / second. Samples were molded into ASTM D638 Type V for tensile testing, ASTM D790 bend bars for dynamic mechanical analysis (DMA), and 61 mm x 61 mm plates for thermomechanical analysis (TMA) testing.

[0067] Tensile testing was completed according to ASTM D638 using a V-shaped tensile bar and an Instron 3365 instrument. All samples were pulled to break at 10 mm / min. An Instron computer program was used to calculate Young's modulus (also known as tensile modulus), tensile strength, and elongation. The results of the tensile testing are shown below in Table 3. Data is presented as an average of four tensile bars. [Table 3]

[0068] As can be seen from Table 3, most samples showed at least a 2-3 times increase in Young's modulus (YM) compared to that of fully fluorinated FEP. The samples also showed increased maximum tensile stress compared to fully fluorinated FEP. Due to the stiffness of Vectra LCP A950, all samples showed reduced elongation compared to fully fluorinated FEP. In terms of CTE values, the CTE values ​​of the test samples were lower than fully fluorinated FEP at both 80°C and 100°C. At 100°C, samples 7-9 and TPL400 had lower CTE values ​​than either fully fluorinated FEP or Vectra LCP A950.

[0069] Samples 7 and 8 and TPL4000 were also tested to calculate flexural modulus, maximum flexural load, and flexural stress. All three-point flexural tests were performed according to ASTM D790-03 using a calibrated Instron testing machine and an ASTM D790 injection molded flexural bar. The samples were placed on two metal rollers spaced 50 mm apart in the Instron testing machine. The rod was used to apply the load at 1.35 mm / min. An Instron computer program was used to calculate the flexural modulus, maximum flexural load, and flexural stress at maximum flexural load. The results of these tests are shown in Table 4 below. All data is expressed as a single flexural bar value.

[0070] Furthermore, for Samples 7 and 8, a test was also carried out to calculate the coefficient of thermal expansion (CTE). The CTE was measured using a 2.0-3.0 μm sample cut from a 61 mm×61 mm injection molded plate with a TA Instruments TMA Q400. The initial dimensions of the sample were measured using a Mitutoyo 293 micrometer. All samples in this Example 3 were measured by the following method. 1. Force 0.100N 2.Equilibrate at 45.00℃ 3. Mark end of cycle 0 4.Ramp 10.00℃ / min to 100.00℃ 5.Isothermal for 5.00min 6. Mark end of cycle 1 7.Ramp 10.00℃ / min to 55.00℃ 8. Mark the end of cycle 2 9.Ramp 5.00℃ / min to 190.00℃ 10. Mark end of cycle 3 11.Jump to 30.00℃ 12. End of method CTE(α) was calculated using the following formula.

number

[0071] As shown in Table 4, Samples 7 and 8 had improved CTE values ​​compared to fully fluorinated FEP, with Sample 8 improving at 80°C, 100°C, 120°C, 150°C, and 180°C. A three-point bend test was used to measure the compatibility of LCP in fully fluorinated FEP. A control was tested without the addition of RPC copolymer. The LCP control sample had a maximum flexural load of 166 and a modulus of 1174 Mpa. When comparing the control to Sample 7, the maximum flexural load and modulus of Sample 7 were significantly lower than the control. These values ​​indicate increased compatibility. Sample 8 has a lower CTE than Sample 7, but retains the flexibility of fully fluorinated FEP.

[0072] 4. Example 4: Mechanical, Electrical, and Thermal Properties of Other FEP / LCP Compatibilized Blends A FEP / LCP compatibilized blend, TPL4000, containing 7.5 wt% Vectra LCP A950 was prepared following the procedure described in Example 2. The mechanical, electrical, and thermal properties of the resulting FEP / LCP compatibilized blend (TPL4000) were tested and compared to FEP and LCP. Tensile, flexural, and CTE tests were performed using the procedures outlined in Example 3.

[0073] CTE was measured with a TA Instruments TMA Q400 using 2.0-3.0 μm samples cut from 61 mm × 61 mm injection molded plates. The initial dimensions of the samples were measured using a Mitutoyo Model 293 micrometer. All samples were measured using the following method. 1. Force 0.100N 2.Equilibrate at 45.00℃ 3. Mark end of cycle 0 4.Ramp 10.00℃ / min to 100.00℃ 5.Isothermal for 5.00min 6. Mark end of cycle 1 7.Ramp 10.00℃ / min to 55.00℃ 8. Mark the end of cycle 2 9.Ramp 5.00℃ / min to 190.00℃ 10. Mark end of cycle 3 11.Jump to 30.00℃ 12. End of method CTE(α) was calculated using the following formula.

number

[0074] Weight loss was measured using 10-20 mg of extruded pellets on a TA Instruments TGA Q500. All samples were measured using the following method. Step 1: Equilibrate at 45℃ Step 2: Ramp 10℃ / min to 800℃ From the results, the 1% weight loss temperature and the 5% weight loss temperature were calculated. Figure 4 is a graph comparing the tensile modulus of the FEP / LCP compatibilized blend with FEP and LCP. As shown in Figure 4, the FEP / LCP compatibilized blend has approximately a three-fold increase in tensile modulus when compared to FEP.

[0075] Figure 5 is a graph showing the CTE of FEP, LCP, and the FEP / LCP compatibilized blend at 100°C. As shown in Figure 5, the CTE of the FEP / LCP compatibilized blend is lower than both unblended polymers (i.e., FEP and LCP). Specifically, the CTE of the FEP / LCP compatibilized blend is nearly half that of both unblended polymers (i.e., FEP and LCP).

[0076] With the improved mechanical and thermomechanical properties, the FEP / LCP compatibilized blends retain good thermal stability. For example, FIG. 6 is a graph showing the thermal stability measured as loss in nitrogen for FEP, LCP, and FEP / LCP compatibilized blends. The Y-axis is the temperature at which 5% weight loss is observed. As shown in FIG. 6, the FEP / LCP compatibilized blends only show a slight decrease in weight loss when compared to FEP. In addition, FIG. 7 is a graph showing the glass transition temperatures of FEP, LCP, and FEP / LCP compatibilized blends. As shown in FIG. 7, the glass transition temperature of the FEP / LCP compatibilized blends is comparable to that of FEP.

[0077] Figures 8 and 9 show the results of the flexural tests. Figure 8 is a graph showing the flexural stress at maximum flexural load for FEP, LCP, and FEP / LCP compatibilized blends. As shown in Figure 8, the maximum flexural load for the FEP / LCP compatibilized blend is lower than the unblended LCP. Figure 9 is a graph showing the flexural modulus for FEP, LCP, and FEP / LCP compatibilized blends. The flexural modulus for the FEP / LCP compatibilized blend is lower than the unblended LCP.

[0078] 5. Example 5: Mechanical and Thermal Properties of Other FEP / LCP Compatibilized Blends Two FEP / LCP compatibilized blends were prepared following the procedure described in Example 2. FEP / LCP compatibilized blends, TG1000 and TG2000, were prepared containing 7.5% and 15.0% by weight of Vectra LCP A950, respectively. The mechanical and thermal properties of the resulting FEP / LCP compatibilized blends were tested and compared to FEP. Tensile, flexural, and CTE tests were performed using the procedures outlined in Example 3.

[0079] The results of the mechanical tensile tests are shown in Figures 10 and 11. Figure 10 is a graph comparing the maximum tensile strength of thin films made from each FEP / LCP compatibilized blend with that of FEP alone. As shown in Figure 10, the second FEP / LCP compatibilized blend (TG2000) has an increased maximum tensile strength compared to FEP alone. Figure 11 is a graph comparing the Young's modulus of thin films made from each FEP / LCP compatibilized blend with that of FEP alone. As shown in Figure 11, the Young's modulus of the FEP / LCP compatibilized blend is about three times that of FEP alone.

[0080] The results of the bending test are shown in Figures 12 and 13. Figure 12 is a graph comparing the maximum bending load of thin films made from each FEP / LCP compatibilized blend with that of FEP alone. As shown in Figure 12, the maximum bending load of the first FEP / LCP compatibilized blend (TG1000) was almost the same as that of FEP. Figure 13 is a graph comparing the bending modulus of thin films made from each FEP / LCP compatibilized blend with that of FEP alone. As shown in Figure 13, the bending modulus of the second FEP / LCP compatibilized blend (TG2000) was the highest, being 2 to 3 times that of FEP.

[0081] The results of the CTE test are shown in Figure 14. Figure 14 is a graph comparing the CTE of thin films made from each FEP / LCP compatibilized blend with that of FEP alone at five temperatures: 80°C, 100°C, 120°C, 150°C, and 180°C. As shown in Figure 14, the CTE of the first FEP / LCP compatibilized blend (TG1000) is lower than that of FEP at all temperatures. The CTE of the second FEP / LCP compatibilized blend (TG2000) is lower than that of FEP at all temperatures except 180°C.

[0082] 6. Example 6: Preparation of PFA / LCP Fibers The sheared perfluoroalkoxyalkane (PFA) was blended with hydroxy-1-naphthoic acid monomer, hydroxybenzoic acid monomer, and liquid crystal polymer (LCP) to produce the reactive polymeric compatibilizer. The percentages of each material are shown in Table 5 below. Once the samples were thoroughly mixed, the mixture was fed into a Leistritz ZSE-18HP-PH twin screw extruder at 4.0-6.0 kg / hr and extruded into pellets. For sample 220E, zones 1-8 were heated to 340°C-360°C. The screw was held constant at 250 RPM. The pellet blend of the compatibilizer blend has a slight grayish color. [Table 5]

[0083] The blend formulations for compatibilization with PFA and LCP are shown in Tables 6 and 7 below. The reactive polymer compatibilizer (sample 220E) prepared above, PFA, LCP, 1,1'-carbonyldiimidazole, and silocym-A nanoparticles were all added to one bag and mixed until homogeneous. No nanoparticles were used in sample 220F as shown in Table 6. The mixture was fed at 4.0-6.0 kg / hr into a Leistritz ZSE-18HP-PH twin screw extruder to extrude the compound into pellets. Zones 1-8 were heated to 340°C-360°C and the screw speed was held constant at 250 RPM. The PFA / LCP blend was obtained as grey pellets. [Table 6] [Table 7]

[0084] PFA / LCP fibers were produced on a Leistriz ZSE27HP twin screw extruder equipped with a 12-hole block die with 0.7 mm hole diameter. The screw speed was held constant at 100 rpm and the feed rate was held constant at 3.0 kg / hr. The melt pressure ranged from 325 to 500 PSI. The temperatures in zones 1 to 12 ranged from 325°C to 350°C. The fibers were air cooled at a pick-up speed of 100 ft / min. The diameters of the resulting fibers were measured to be between 0.09 mm and 0.2 mm.

[0085] 7. Example 7: Mechanical properties of PFA / LCP fibers Each fiber was attached to a paper mount using Staples Glue Tape Permanent at a gauge length of 30 mm according to ASTM D3379-75. A secondary line of Staples Glue Tape Permanent and a piece of paper was used to hold the fiber in place to prevent the Instron grips from rubbing directly against the fiber. Fiber diameter was measured for each sample using a Ziess SteREO Discovery V.12 microscope. Mechanical properties of fluoropolymer and fluoropolymer alloy fibers were measured using an Instron 5582 universal testing machine. The Instron was equipped with a 1 kN load cell and wedge grips. Once each sample was placed in the wedge grips, the fiber mount was cut with scissors. Tensile tests were performed until break at an extension rate of 50 mm / min. Tensile strength, tensile modulus, and elongation were calculated using BlueHill 2 software.

[0086] Table 7 shows the mechanical properties of fibers made from pure PFA and PFA / LCP compatibilized blends (see Table 6A) at room temperature. As shown in Table 7 below, the addition of 7.5% by weight of LCP dramatically increased the tensile strength and tensile modulus. Sample 220F had a tensile strength 3.2 times higher than PFA and a Young's modulus 9.4 times higher than PFA. The elongation of the PFA / LCP blend was reduced compared to pure PFA. This is likely due to the high crystallinity of LCP, which reduced the elasticity of the blend. However, the addition of a small amount of nanoparticles to Sample 220G broke the crystalline regions of the LCP polymer in the blend, increasing the elongation compared to Sample 220F, which did not contain nanoparticles. [Table 8]

[0087] 8. Example 8: Electrical Properties of PFA / LCP Compatibilized Blends In this example, the electrical properties of the following samples were tested: a pure PFA sample, samples 220F and 220G (their formulations are shown in Table 6A), 141D, 143B, 147D, and 149E (their formulations are shown in Table 6B). For each sample, the sample thickness was measured at 4-5 points using a digital caliper and averaged. The sample was then inserted into the cavity. The measurements were performed using a Keysight P9374A PNA and NIST SplitC software. For defective samples, the best area was used to cover the cavity opening.

[0088] The electrical properties of each sample are shown in Table 8 below. More specifically, Table 8 shows the dielectric constant and dielectric loss at 17 GHz for pure PFA and PFA / LCP compatibilized blends (samples 220F and 220G). As shown in Table 8, the dielectric constant of the PFA / LCP compatibilized blend is higher than that of pure PFA. The dielectric loss of the PFA / LCP compatibilized blend is also higher than that of pure PFA. [Table 9]

[0089] 9. Example 9: Preparation of other PFA / LCP compatibilized blends PFA / LCP RPC copolymers were prepared. Sheared PFA, Vectra LCP A950, 6-hydroxy-2-naphthoic acid, and 4-hydroxybenzoic acid were all added to one bag and mixed uniformly. The amounts of each material are shown in Table 9 below. Both LCP monomers 6-hydroxy-2-naphthoic acid and 4-hydroxybenzoic acid were added at 1:1 molar equivalents, with a total of 5 wt% for all formulations. Once the samples were thoroughly mixed, the mixtures were fed into a Leistritz ZSE18HP at 4.0-6.0 kg / hr. For each sample, zones 1-8 were heated to 310°C-340°C. The screw speed was held constant at 250 rpm. PFA / LCP RPC copolymers were also prepared in the presence or absence of PFA. All RPC copolymers were obtained as brown pellets. [Table 10]

[0090] FIG. 15 shows an example of a scheme for producing PFA / LCP RPC copolymer. As shown in FIG. 15, PFA / LCP RPC copolymer is prepared by polycondensation in a twin screw extruder. Step-growth polycondensation proceeds with the heat of the extruder. HF generated from PFA and / or sheared PFA acts as a Lewis acid to drive the reaction. Aromatic monomers 6-hydroxy-2-naphthoic acid and 4-hydroxybenzoic acid are common LCP monomers and are effective in reducing the interfacial tension between PFA and LCP. Since 6-hydroxy-2-naphthoic acid and 4-hydroxybenzoic acid are AB-type functional monomers, any monomer can be polymerized with other molecules or other monomers in the sample molecular structure. The corresponding random copolymers, monomers, and oligomers can react with the end groups of sheared PFA and Vectra LCP A950 to produce random block copolymers.

[0091] To prepare the PFA / LCP compatibilized blends, carbonyldiimidazole (CDI), Vectra LCP A950, RPC copolymer, and pure PFA were all added to one bag and mixed until homogenous. The amounts of CDI, Vectra LCP A950, RPC copolymer, and pure PFA used for each sample are shown in Table 10 below. The mixture was then fed at 4.0-6.0 kg / hr into a Leistritz ZSE18HP. Zones 1-8 were heated to 310°C-340°C. The screw speed was held constant at 250 rpm. The PFA / LCP blends were obtained as off-white pellets. [Table 11]

[0092] 10. Example 10: Mechanical Properties of PFA / LCP Compatibilized Blends The sample from Example 9 was gravity fed into a Sumitomo SE75DU injection molding machine. The feed zone was held at 49°C. Zones 1-5 in the rotating screw were heated to 310-340°C. The fill time was 5.00 seconds and the fill pressure was 10.00 kpsi. The screw was retracted 0.3 inches at a rate of 0.2 in / sec. Samples were molded into ASTM D638 V-type for tensile testing, ASTM D790 bend bars for dynamic mechanical analysis (DMA), and 61 mm x 61 mm plates for thermomechanical analysis (TMA) testing.

[0093] For tensile testing, all mechanical testing of injection molded samples was performed using a V-shaped tensile bar. All tensile tests were completed according to ASTM D638 using a V-shaped tensile bar and an Instron 3365 type machine. All samples were pulled to failure at 10 mm / min. An Instron computer program was used to calculate Young's modulus (YM), tensile strength, and elongation. All data are presented as an average of four tensile bars.

[0094] For thermomechanical analysis (TMA), the coefficient of thermal expansion (CTE) was measured with a TA Instruments TMA Q400 using 2.0-3.0 μm samples cut from 61 mm × 61 mm injection molded plates. The initial dimensions of the samples were measured using a Mitutoyo Model 293 micrometer. All samples were measured using the following method. 1. Force 0.100N 2.Equilibrate at 45.00℃ 3. Mark end of cycle 0 4.Ramp 10.00℃ / min to 100.00℃ 5.Isothermal for 5.00min 6. Mark end of cycle 1 7.Ramp 10.00℃ / min to 55.00℃ 8. Mark the end of cycle 2 9.Ramp 5.00℃ / min to 190.00℃ 10. Mark end of cycle 3 11.Jump to 30.00℃ 12. End of method CTE(α) was calculated using the following formula.

number

[0095] Table 11 shows the tensile properties of the PFA / LCP compatibilized blends. The formulations of Samples 897A-C are shown in Table 10 above. As shown in Table 11 below, Sample 897A had the highest maximum tensile at 21 MPa. Sample 897B had the highest Young's Modulus (YM) at 826 MPa, but had only a slight improvement in elongation compared to the PFA / LCP formulation of Sample 897C. Both formulations had an increased YM compared to pure PFA. Samples 897A and 897B had a slight improvement in maximum tensile when compared to pure PFA. [Table 12]

[0096] Table 12 below shows the coefficient of thermal expansion (CTE) values ​​of Samples 897A-C, pure PFA, and LCP Vectra A950. Samples 897A and 897B had higher CTE values ​​at 80°C and 100°C compared to Sample 897C, pure PFA, and LCP Vectra A950. Sample 897C had CTE values ​​of 138 ppm / °C and 141 ppm / °C at 100°C and 120°C, respectively, with the CTE values ​​increasing at higher temperatures (150°C and 180°C). At 180°C, Sample 897B had a CTE value of 117 ppm / °C, which is lower than the CTE value of LCP Vectra A950 at 180°C. [Table 13]

[0097] The following Tables 13 and 14 show the storage modulus and glass transition temperature of PFA and PFA / LCP compatibilized blends. As shown in Table 13, the PFA / LCP compatibilized blends showed higher storage modulus values ​​than pure PFA. In addition, as shown in Table 14, the glass transition temperature of the PFA / LCP compatibilized blends was lower than that of pure PFA. [Table 14] [Table 15]

[0098] Example 11: Other compatibilizer formulations In the above Examples 1-10, all of the reactive polymer compatibilizers used fluorinated polymers and non-fluorinated monomers. In addition to these classes of materials, monomers or polymers can be added to impart molecular flexibility to the RPC copolymer. These linking molecules may have flexible moieties such as aliphatic chains or ether functionalities. These linking molecules may also contain reactive functionalities such as amines. Linking molecules are used to chemically bond the LCP monomers to the polymer backbone. This allows the molecularly rigid polymerized LCP units, known as mesogens, to be flexible and aligned with each other, providing mechanical strength and localized domains that are compatible with the LCP polymer.

[0099] In some embodiments, non-fluorinated RPC copolymers may be used to compatibilize LCP / FP blends. To produce non-fluorinated RPC copolymers, non-fluorinated polymers are combined with non-fluorinated monomers. In some embodiments, non-fluorinated linking molecules may be used. In some preferred embodiments, the non-fluorinated polymer contains reactive functional groups such as carboxylic acid, hydroxy, ester, and anhydride, and the non-fluorinated monomer is preferably selected from LCP monomers such as 6-hydroxy-2-naphthoic acid and 4-hydroxybenzoic acid. Non-fluorinated polymers suitable for this purpose include, but are not limited to, copolymers of cyclic olefins (COC) as depicted in FIG. 16.

[0100] Examples of RPC copolymer formulations are shown in Table 15. Values ​​are expressed as weight percent of the initial mixture. In this Example 11, each polymer contains reactive functional groups such as carboxylic acid, hydroxy, ester, COF, or anhydride. Such functional groups may be present only as terminal groups, i.e., at the ends of the polymer chain, or may be present throughout the polymer chain. In this Example 11, the linking molecules comprise SEBS (styrene-ethylene-butadiene-styrene) thermoplastic elastomer rubber functionalized with amine reactive groups and 2,2-bis[4-(4-aminophenoxyphenyl)]hexafluoropropane. In this Example, the LCP monomers 6-hydroxy-2-naphthoic acid and 4-hydroxybenzoic acid are used in a 1:1 molar ratio. [Table 16]

[0101] For each sample in this example, the ingredients were mixed and fed into a co-rotating twin screw extruder with the temperature profile shown in Table 16. Zone 1 is near the feeder and Zone 8 is the die. The material was fed into the extruder at 5.5 kg / hr and the extruder motor was running at 300 RPM. The extrudate was cooled in a water bath and pelletized. [Table 17]

[0102] Example 12: Blends of LCP and Fluoropolymer with Compatibilizer The RPC copolymer described in Example 11 can be used to compatibilize the liquid crystal polymer and fluoropolymer blends. In addition, a linking molecule such as functionalized SEBS rubber can be added to the LCP / FP blend. In some embodiments, other molecules can be used in addition to the RPC copolymer to improve the compatibility of the LCP with the fluoropolymer. In some embodiments, the molecule is 1,3-bis(4,5-dihydro-2-oxazolyl)benzene, although molecules with various functional groups are also effective. Table 17 shows some example compositions of LCP / FP blends. In these blends, the fluoropolymer may or may not have reactive functional groups. [Table 18]

[0103] All materials in Table 17 were fed into a co-rotating twin screw extruder at 5.5 kg / hr with the extruder motor running at 300 RPM. Extruder temperatures are shown in Table 18. The extrudate was cooled in a water bath and pelletized prior to injection molding. All samples were injection molded at barrel temperatures between 600 and 626°F. [Table 19]

[0104] The tensile strength, tensile modulus, and elongation of injection molded parts of these blends were measured, as shown in Figures 17-19. For clarity, the elongation at break of PFA (485.6% ± 8.92%) has been omitted. V-bend bars were injection molded and tested using an Instron universal testing machine at a strain rate of 10 in / min. Unless otherwise noted, all results are reported as the average of five samples, and error bars represent one standard deviation. In addition, the CTE (Z-direction) of these samples was measured using a thermomechanical analyzer (TMA). The CTE was measured as the slope of the line that best fits the data over a given temperature range. These results are presented in Figure 20.

[0105] Split cavity dielectric measurements were also performed to measure the Dk and Df of these materials at 16 GHz. The results are presented in Figures 21 and 22. The PFA samples reported in this and the following examples were pure PFA and were injection molded at 725-770°F. Sample 92F did not form strands upon extrusion and could not be pelletized or injection molded, so those results are not reported.

[0106] All of the samples in this Example 12 had higher tensile strength and tensile modulus than PFA alone. All of the samples also had lower elongation than PFA alone. Comparing 90A to 92E, it was found that the tensile strength of the 90A blend was higher. As can be seen from the lower elongation of 92A compared to 90A, the addition of functionalized SEBS rubber to the final blend did not improve these properties. All of the embodiments examined in this Example 12 had lower CTE at 100 to 200°C than PFA alone.

[0107] Sample 90A showed the greatest improvement in properties. As already mentioned, 90A has better mechanical properties than 92E and a lower CTE from 10 to 100 °C than sample 92A. In addition, SEM images were taken of selected samples. These results are presented in Figures 23 to 25. These micrographs show that the presence of RPC82A improves the compatibility of the LCP / FP blends. The microstructures of 92C and 92D show significantly more texture than 90A. This shows that sample 90A has lower surface tension between LCP and PFA and smaller LCP and PFA domains. The lower surface tension is likely due to the RPC. In addition, the absence of RPC leads to a higher dielectric constant as seen in Figure 21. The use of a small molecule compatibilizer alone does not appear to reduce the surface tension between PFA and LCP as shown in sample 92C.

[0108] Example 13: Use of Various Reactive Polymeric Compatibilizers in LCP / Fluoropolymer Blends Because reactive polymeric compatibilizers are useful for effectively blending LCPs with fluoropolymers, examples of fluoropolymer / LCP blends were made using each of the reactive polymeric compatibilizers discussed in Example 11. Table 19 shows the compositions of some of the LCP and fluoropolymer blends that were compatibilized with the RPCs discussed in Example 11. [Table 20]

[0109] All materials in Table 19 were mixed and fed into a co-rotating twin screw extruder at 5.5 kg / hr with the extruder motor running at 300 RPM. The extruder temperatures are shown in Table 20. The extrudate was cooled in a water bath and pelletized. Samples were then injection molded. All samples were injection molded at barrel temperatures between 600 and 626°F. [Table 21]

[0110] The tensile properties of injection molded parts of these blends were measured as shown in Figures 26-28. V-bend bars were injection molded and tested using an Instron universal testing machine at a strain rate of 10 in / min. Additionally, the CTE (Z-direction) of these samples was measured using a thermomechanical analyzer (TMA). These results are shown in Figures 29 and 30. In Figure 29, the dimensional changes have been shifted vertically so that all the curves are aligned around 25°C for better understanding. The slope of each curve corresponds to the coefficient of thermal expansion (CTE) over that temperature range. Split cavity dielectric measurements were also performed to measure the Dk and Df of these materials. These results are shown in Figures 31 and 32.

[0111] Of these samples, sample 85A had the highest tensile strength and elongation at break. Of the FEP-based samples, sample 88A had the lowest tensile strength and elongation at break, while 88B and 88C behaved similarly to each other. Samples 85C and 88A shrunk significantly above 100°C. This suggests that the presence of 82C reactive polymer compatibilizer leads to shrinkage at higher temperatures. The CTE of each embodiment at 100-200°C is lower than that of the corresponding fluoropolymer alone. Nevertheless, the Z-direction CTE is still relatively high. In terms of dielectric properties, sample 85A has the lowest Dk and Df among the PFA-based samples. All of the FEP-based samples have lower dielectric loss than the PFA-based samples.

[0112] Example 14: Ratio of LCP to Fluoropolymer In Example 13, it was found that there are many RPCs that can compatibilize LCP and fluoropolymer. However, in Example 13, only one ratio of fluoropolymer to LCP was examined. RPCs can compatibilize a wide range of LCP / fluoropolymer compositions. The compositions of the samples in this Example 14 are shown in Table 21. It should be noted that Sample 90A has the same composition and processing conditions as Sample 85A, but the number of processing times is different. The samples in this Example 14 were mixed and fed into a twin screw extruder at 5.5 kg / hr. The extruder was operated at 300 RPM. The temperatures used were as shown in Table 20 for Samples 85A-C. [Table 22]

[0113] These samples were also injection molded under the conditions described in Example 13 and their tensile properties were similarly measured. The tensile properties of these materials are shown in Figures 33-35. The tensile properties of sample 85D are not reported because it was too slippery and slipped through the tensile grips of the Instron universal testing machine. The flexural properties of all samples, including 85D and the LCP alone, were measured and are reported in Figure 36. The flexural and tensile moduli of materials have been found to generally be linearly correlated, allowing inferences to be made from the flexural modulus about the tensile modulus and other mechanical properties.

[0114] The flexural modulus of PFA was previously measured and was 399 MPa. Taking this into account, along with the measured flexural modulus of LCP (6602), one can predict what the flexural modulus of the LCP / PFA blends would be if the flexural modulus were proportional to a weighted average of only the LCP and PFA components. The predicted flexural modulus values ​​for these embodiments are shown in Table 22. Note that the amount of PFA used in this calculation includes the PFA in the reactive polymer compatibilizer, but does not include the other compatibilizing components (totaling 2% by weight of the blend). Comparing these data with FIG. 36, it was found that the actual flexural modulus of each blend was higher than the predicted value when only PFA and LCP were considered. Thus, it was demonstrated that the compatibilizer contributes significantly to the mechanical strength of the LCP / PFA blends. [Table 23]

[0115] The dielectric properties of these embodiments were measured at 16 GHz using the split cavity technique. The dielectric constant and dielectric loss of these embodiments are shown in Figures 37 and 38, respectively. There was a trend that the higher the LCP content of the sample, the higher the Df of the sample. Therefore, the most desirable sample depends on the application in which it will be used. For bending applications, sample 90A would be desirable, while for applications requiring mechanical strength, sample 85D would be more desirable.

[0116] E. conclusion

[0117] Compositions and methods of making liquid crystal polymer and fluoropolymer blends are disclosed. Disclosed embodiments of the methods of blending these polymers include synthesis and / or use of reactive polymer compatibilizers and, in some embodiments, small molecule compatibilizers. Reactive polymer compatibilizer embodiments are made by combining at least one polymer with at least one monomer. In some embodiments, one of the polymers is a fluoropolymer, which may be a functionalized fluoropolymer containing reactive groups. However, in some embodiments, the polymer may be a non-fluorinated polymer, such as a cyclic olefin copolymer. The other component of reactive polymer compatibilizer embodiments is a non-fluorinated monomer. In some embodiments, these non-fluorinated monomers are LCP monomers. In some embodiments, a linking molecule may be added to improve the molecular flexibility of the reactive polymer compatibilizer, allowing the LCP mesogens that are constructed to align more easily.

[0118] It will be understood that certain elements in the disclosed embodiments of the present invention may be embodied in a single structure, a single step, or a single material, etc. Likewise, certain elements in the disclosed embodiments may be embodied in multiple structures, steps, or materials, etc.

[0119] The above description illustrates and describes the methods, apparatus, products, compositions, and other teachings of the present disclosure. In addition, the present disclosure shows and describes only certain embodiments of the disclosed methods, apparatus, manufactures, compositions, and other teachings. However, as noted above, it will be understood that the teachings of the present disclosure can be used in various other combinations, variations, and environments, and can be modified and varied within the scope of the teachings described herein, consistent with the skill and / or knowledge of those of ordinary skill in the art. Furthermore, the embodiments described herein above are intended to illustrate certain best modes known for implementing the methods, apparatus, products, compositions, and other teachings of the present disclosure, and to enable others of ordinary skill in the art to utilize the teachings of the present disclosure in such or other embodiments, and with various modifications required for a particular application. Thus, the methods, apparatus, products, compositions, and other teachings of the present disclosure are not intended to be limited to the exact embodiments and examples disclosed herein. The headings herein are intended merely to correspond with the suggestions of 37 C.FR §1.77 or to provide organizational queues, and are not intended to limit or characterize the invention described herein.

Claims

1. A polymer blend comprising a fluoropolymer, a liquid crystal polymer, and a compatibilizer composition, and at least one selected from the group consisting of a small molecule compatibilizer and a binding molecule, The compatibilizer composition comprises a copolymer comprising a fluorine-containing molecule and a liquid crystal monomer; the liquid crystal monomer is at least one selected from the group consisting of hydroxynaphthoic acid and hydroxybenzoic acid; The small molecule compatibilizer is at least one selected from the group consisting of a bis(oxazoline) compound, a carbonyldiimidazole compound, and an epoxy compound; The binding molecule is a polymer blend that is at least one selected from the group consisting of SEBS (styrene-ethylene-butadiene-styrene) thermoplastic elastomer rubber functionalized with amine reactive groups and 2,2-bis[4-(4-aminophenoxyphenyl)]hexafluoropropane.

2. 2. The polymer blend of claim 1, wherein the binding molecule is a styrene-ethylene-butadiene-styrene rubber.

3. 2. The polymer blend of claim 1, wherein said linking molecules are attached to both said fluorine-containing molecules and said liquid crystal monomers.

4. 10. The polymer blend of claim 1, wherein the compatibilizer composition further comprises a fully fluorinated fluoropolymer selected from fluorinated ethylene propylene (FEP) and perfluoroalkoxyalkane (PFA).

5. The polymer blend of claim 1 , wherein the polymer blend comprises at least 15% by weight of the liquid crystalline polymer.

6. 2. The polymer blend of claim 1, wherein the fluoropolymer is fluorinated ethylene propylene (FEP).

7. 2. The polymer blend of claim 1, wherein the fluoropolymer is a perfluoroalkoxyalkane (PFA).

8. 8. The polymer blend of claim 7, wherein the polymer blend comprises at least 65% by weight of the PFA and at least 15% by weight of the liquid crystalline polymer.

9. The polymer blend of claim 7, wherein the polymer blend comprises about 68-72% by weight of the PFA, about 17-20% by weight of the liquid crystal polymer, and about 8-12% by weight of the compatibilizer composition.

10. 10. The polymer blend of claim 1, wherein the liquid crystalline polymer is of the same type as the liquid crystalline monomer of the compatibilizer composition.

11. 10. The polymer blend of claim 1, wherein the polymer blend has a flexural modulus that is at least 800% of the flexural modulus of the fluoropolymer alone.

12. A polymer blend comprising a fluoropolymer, a liquid crystal polymer, and a compatibilizer composition, and at least one selected from the group consisting of a small molecule compatibilizer and a binding molecule, The compatibilizer composition comprises a copolymer comprising perfluoroalkoxyalkane (PFA) molecules and at least two different liquid crystal monomers; the liquid crystal monomer is at least one selected from the group consisting of hydroxynaphthoic acid and hydroxybenzoic acid; The small molecule compatibilizer is at least one selected from the group consisting of a bis(oxazoline) compound, a carbonyldiimidazole compound, and an epoxy compound; The binding molecule is a polymer blend that is at least one selected from the group consisting of SEBS (styrene-ethylene-butadiene-styrene) thermoplastic elastomer rubber functionalized with amine reactive groups and 2,2-bis[4-(4-aminophenoxyphenyl)]hexafluoropropane.

13. 13. The polymer blend of claim 12, wherein the liquid crystal monomers include 6-hydroxy-2-naphthoic acid and 4-hydroxybenzoic acid.

14. 13. The polymer blend of claim 12, wherein the compatibilizer composition further comprises a styrene-ethylene-butadiene-styrene thermoplastic elastomer rubber.

15. 13. The polymer blend of claim 12, wherein the polymer blend has an ultimate tensile strength greater than a pure composition of PFA.

16. 13. The polymer blend of claim 12, wherein the polymer blend has a lower coefficient of thermal expansion at 100-200° C. than the pure composition of PFA.

17. 13. The polymer blend of claim 12, wherein the polymer blend has a percent elongation at break of at least 15%.

18. A polymer blend comprising a fluoropolymer, a liquid crystal polymer, and a reactive polymeric compatibilizer copolymer, The reactive polymeric compatibilizer copolymer is formed by the reaction of a functionalized fluoropolymer, a linking molecule, and at least one LCP monomer; The LCP monomer is at least one selected from the group consisting of hydroxynaphthoic acid and hydroxybenzoic acid, The binding molecule is a polymer blend that is at least one selected from the group consisting of SEBS (styrene-ethylene-butadiene-styrene) thermoplastic elastomer rubber functionalized with amine reactive groups and 2,2-bis[4-(4-aminophenoxyphenyl)]hexafluoropropane.

Citation Information

Patent Citations

  • Thermomeltable fluororesin composite

    JP2001181463A

  • Compatibilizers for fluoropolymers and polyolefins; blends thereof

    US20050197460A1

  • Highly filled unsaturated fluoropolymer compositions for cables

    US20070078209A1

  • Polyolefin compatibilizer composition for compounding to improve stiffness and impact balance

    US20180015647A1